Association analysis of CYP2A6 polymorphism to sudden and unexpected death of infants. Issue 2 (2015) - Osawa, Motoki; Inaoka, Yoshihiko; Nakatome, Masato; Miyashita, Keiko; Ochiai, Eriko; Kakimoto, Yu; Satoh, Fumiko; Matoba, Ryoji
No abstract available